Horror movie : a novel - Tremblay, Paul (William Morrow, an imprint of HarperCollins Publishers, 2024)
The only surviving cast member of a notorious, disturbing 1993 art house horror movie joins the remake, but begins having trouble distinguishing between reality and film in the new novel by the author of The Pallbearers Club.